2002
DOI: 10.1073/pnas.032678499
|View full text |Cite
|
Sign up to set email alerts
|

Importance of epidermal growth factor receptor signaling in establishment of adenomas and maintenance of carcinomas during intestinal tumorigenesis

Abstract: We used the hypomorphic Egfr wa2 allele to genetically examine the impact of impaired epidermal growth factor receptor (Egfr) signaling on the Apc Min mouse model of familial adenomatous polyposis. Transfer of the Apc Min allele onto a homozygous Egfr wa2 background results in a 90% reduction in intestinal polyp number relative to Apc Min mice carrying a wild-type Egfr allele. This Egfr effect is potentially synergistic with the actions of the modifierof-min (Mom1) locus. Surprisingly, the size, expansion, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
184
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(202 citation statements)
references
References 37 publications
16
184
0
2
Order By: Relevance
“…The fact that the mean EGFr content is higher in normal mucosa than in neoplastic tissue, both for protein and mRNA determination, does not exclude a role for EGFr in the carcinogenesis of CRC. Epidermal growth factor receptor signalling in the maintenance of carcinomas during intestinal tumorigenesis has been found in animal experiments (Roberts et al, 2002). In our study, the inverse relationship between EGFr expression and activity, demonstrated so far in CRC cell lines (Keese et al, 2005), supports the hypothesis that activated EGFr has a role in CRC.…”
Section: Discussionsupporting
confidence: 86%
“…The fact that the mean EGFr content is higher in normal mucosa than in neoplastic tissue, both for protein and mRNA determination, does not exclude a role for EGFr in the carcinogenesis of CRC. Epidermal growth factor receptor signalling in the maintenance of carcinomas during intestinal tumorigenesis has been found in animal experiments (Roberts et al, 2002). In our study, the inverse relationship between EGFr expression and activity, demonstrated so far in CRC cell lines (Keese et al, 2005), supports the hypothesis that activated EGFr has a role in CRC.…”
Section: Discussionsupporting
confidence: 86%
“…However, overexpression causes apoptotic resistance and tumor propagation, especially in colorectal carcinogenesis. 23,24 Therefore, our finding of EGFR amplifications seems to identify cells that drive tumor formation and propagation. Interestingly, such amplifications were accompanied by deletions of SMAD7.…”
Section: Discussionmentioning
confidence: 95%
“…40,41 In Apc Min/1 mice expressing a mutant epidermal growth factor receptor, polyp number was reduced 90% compared to mice with wild-type receptor. 42 In a mouse xenograft model, treatment with an inhibitor of the upstream kinase MEK suppressed tumor growth, 43 providing further evidence of the importance of the ERK signaling pathway in colon cancer. The impact of GC-C deficiency on this pathway may be one of the alterations leading to increased apoptosis in the intestine of Apc Min/1 ; Gucy2c 2/2 mice.…”
Section: Discussionmentioning
confidence: 96%